ANALISIS PORTOFOLIO OPTIMAL MODEL INDEKS TUNGGAL SAHAM INDEKS ENERGY PERIODE 2016 – 2021 - Hasyim Mulya Abdillah; Renea Shinta Aminda; Immas Nurhayati (Institut Teknologi dan Bisnis Dewantara, 2023)
Investment is the activity of investing capital in the present with the aim of getting profits in the future. A realistic investor will invest his funds in stocks that have high returns but with low risk. To minimize a risk, an optimal portfolio is formed. The optimal portfolio is a combination of expected return with minimal risk. The single index model underlies that the market price index is in line with the price of securities. This study aims to determine the return and risk, as well as to choose the optimal portfolio and the proportion of funds in the Energy Sector Index stocks on the Indonesia Stock Exchange. The results showed that there were 5 stocks included in the optimal portfolio with the proportion of funds for each stock, namely HRUM by 2%, MEDC by 10%, INDY by 7%, DOID by 80% and PTRO by 1%. With an expected return of 3.4% and a risk of 8.1%. Careful investors can diversify portfolios rather than investing entirely in individual stocks, to minimize risk.